2023
DOI: 10.3389/fendo.2022.1060301
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral multifocality is an independent predictor of patients’ outcome in Middle Eastern papillary thyroid carcinoma

Abstract: BackgroundTumor multifocality is frequently seen in Papillary thyroid carcinoma (PTC). However, few studies have analysed the impact of bilateral multifocality in PTC. The incidence of bilateral multifocality, its clinico-pathological associations and prognostic impact in PTC from Middle Eastern ethnicity remains unestablished.MethodsWe retrospectively evaluated 1283 patients who underwent total thyroidectomy for PTC. Bilateral and unilateral multifocality were decided based on the final pathology result. Prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…In this study, elderly PTC patients with microcalcifications had a LLNM incidence of 24.5%, significantly higher than those without this risk feature. For elderly PTC patients with existing CLNM, bilateral lesions are a significant LLNM risk factor that should not be overlooked, consistent with findings from multiple studies ( 34 , 35 ). In this study, 14 elderly PTC patients developed LLNM in the absence of CLNM, which accounts for nearly 25% of LLNM cases, aligning with previous research findings ranging from 5% to 25% ( 36 , 37 ), this underscores the importance of preoperative assessment and warrants further investigation into the necessity of central compartment dissection in this subgroup.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, elderly PTC patients with microcalcifications had a LLNM incidence of 24.5%, significantly higher than those without this risk feature. For elderly PTC patients with existing CLNM, bilateral lesions are a significant LLNM risk factor that should not be overlooked, consistent with findings from multiple studies ( 34 , 35 ). In this study, 14 elderly PTC patients developed LLNM in the absence of CLNM, which accounts for nearly 25% of LLNM cases, aligning with previous research findings ranging from 5% to 25% ( 36 , 37 ), this underscores the importance of preoperative assessment and warrants further investigation into the necessity of central compartment dissection in this subgroup.…”
Section: Discussionsupporting
confidence: 88%
“…Recent guidelines and consensus statements recommended thyroid lobectomy in the majority of patients with PTC, although total thyroidectomy should be performed for bilateral thyroid cancer [18,25]. Previous reports indicated that bilaterality was associated with aggressive clinicopathologic features, including a larger tumor diameter, ETE, and LN metastasis, as well as a higher TNM stage at presentation [14,26]. In contrast, Kim et al indicated that the clinicopathologic characteristics were not significantly different between the patients with multifocal-bilateral and multifocal-unilateral PTC [12].…”
Section: Discussionmentioning
confidence: 99%